The Political Economy of Germany's 'Agenda 2010' Reforms: Insights from an Augmented Veto Player Model - Maximilian A. Freier (London School of Economics and Political Science (LSE), European Institute, 2022)
Germany's 'Agenda 2010' labour and welfare reforms contradict conventional wisdom that its political economy with many veto players disallows paradigmatic structural change. To address this puzzle, this paper presents an augmented version of the Veto Player Model. Introducing veto clusters to the model allows to map Germany's complex political economy structure with many interlocking and overlapping actors and institutions, and to better understand the dynamics of changing policy preferences. The paper shows that three veto cluster - corporatist interests, the federal governance structure and the lack of cohesion within the federal government - alternately blocked reform in Germany between 1983 and 2002. Only in 2003, when the blocking power of all these constraints waned, was it possible for the federal government to implement far-reaching socio-economic reforms.
Keywords: 330; Agenda 2010; Germany; Augmented Veto Player Model